DAMPAK PANDEMI COVID 19 TERHADAP PENDAPATAN USAHATANI BAWANG PUTIH (Allium Sativum) DI KECAMATAN SEMBALUN - M. Kholis Kholis (Fakultas Pertanian, Universitas Gunung Rinjani, 2022)
Central Bureau of Statistics of West Nusa Tenggara released that in February 2021, almost all farmers experienced a decrease in the exchange rate of farmers, including horticultural farmers. This study aimed to determine the impact of the COVID-19 pandemic and the constraints farmers face in garlic farming in Sembalun District as a centre of garlic production nationally. The was used qualitative descriptive method by determining 30 respondents who did garlic farming before and during the covid 19 pandemic. Based on the results, the income of garlic farmers in Sembalun District before the Covid-19 pandemic was significantly different from that of garlic farming during the pandemic. Meanwhile, the biggest obstacle faced by garlic farmers was price fluctuations, and marketing was due to the need for a good market chain. Keywords: Garlic, The Covid-19, Income, Sembalun, Farming